Where injustices (fail to) meet: newspaper coverage of speciesism, animal rights, and racism - Kinefuchi, Etsuko (Frontiers in Communication, 2024)
This study examines the ways widely circulated U.S. newspapers have articulated the idea of "speciesism" and its associated idea "animal rights" in relation to "racism" to understand how powerful news media helps to shape the public understanding of the interlocking systems of oppression that cuts across the human and the more-than-human world. The archives (1987 to 2023) of three U.S. newspapers -The New York Times, USA Today, and The Washington Post -were analyzed, using qualitative content analysis. The ideas of articulation, symbolic annihilation, erasure, and discursive closure served as the analytical guides for the analysis. The analysis shows that there is gross underrepresentation of speciesism and even far less representation of the relationship between speciesism and racism and between animal rights and anti-racism. When represented, the articulations showed problematic patterns of erasure of those concepts and relationships. The paper ends with the implications of the findings.